Logic gate behavior and intracellular application of a fluorescent molecular switch for the detection of Fe3+ and cascade sensing of F- in pure aqueous media - Dwivedi R.; Singh D.P.; Singh S.; Singh A.K.; Chauhan B.S.; Srikrishna S.; Singh V.P. (My University, 2025)
The nature and coordination sites of the Schiff base 3,3′-(1E,1′E)-(1,3-phenylenebis(azan-1-yl-1-ylidene))bis(methan-1-yl-1-ylidene)dinaphthalen-2-ol (APHN) were tuned by its selective reduction to design a highly efficient fluorescent probe, 3,3′-(pyridine-2,6-diylbis(azanediyl))bis(methylene)dinaphthalen-2-ol (RAPHN). The structures of APHN, RAPHN, and the RAPHN-Fe3+ complex were satisfactorily modeled from the results of density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations. RAPHN worked in pure aqueous medium as a turn on-off-on probe of Fe3+ and F-. The fluorescence nature of the probe in the presence and absence of Fe3+/F- was regulated by a set of mechanisms including -CHN isomerization and LMCT. A 2:1 (M:L) binding stoichiometry was established from a fluorescence Job's plot and further substantiated from HR-MS studies. The limits of detection of RAPHN for Fe3+ and RAPHN-Fe3+ for F- were found to be 2.49 × 10-7 M and 1.09 × 10-7 M, respectively. The RAPHN probe caused no cytotoxicity in gut tissue of Drosophila even at high concentrations. The probe displayed excellent bioimaging applications for detection of Fe3+ and F- in gut tissue of Drosophila. A combinatorial logic gate was constructed for the proper understanding of the working principle of RAPHN. © 2019 The Royal Society of Chemistry.